PENGARUH RETURN ON ASSET DAN EARNING PER SHARETERHADAP HARGA SAHAM PADA PT ADHI KARYA TbkPERIODE 2013 – 2023 - Hendri Prabowo; Supatmin Supatmin (LAP4B, 2026)
This study aims to analyze the effect of Return on Asset (ROA) and Earning per Share (EPS) on the stock price of PT Adhi Karya Tbk during the period 2013 to 2023. The rapid growth of the construction sector in Indonesia, particularly in the context of national infrastructure development, makes state-owned construction companies such as PT Adhi Karya Tbk a highly relevant object of study from the perspective of financial performance and capital market dynamics. The research method used is a quantitative approach with an associative design, utilizing secondary data in the form of audited annual financial reports and closing stock price data from the Indonesia Stock Exchange (IDX). The analytical techniques applied include classical assumption tests (normality, multicollinearity, heteroscedasticity, autocorrelation), multiple linear regression analysis, coefficient of determination test (R²), partial test (t-test), and simultaneous test (F-test), all processed using SPSS software version 25. The results show that ROA partially does not have a significant effect on stock prices (t-count 0.495 < t-table 2.365; sig. 0.636 > 0.05), and EPS also does not have a significant effect (t-count 0.174 < t-table 2.365; sig. 0.867 > 0.05). Simultaneously, ROA and EPS also do not have a significant effect on stock prices (F-count 1.136 < F-table 4.74; sig. 0.374 > 0.05), with a coefficient of determination of 24.5%, meaning 75.5% of stock price movements are influenced by other variables outside this model. These findings indicate that investors in the Indonesian capital market consider broader fundamental factors in making investment decisions on PT Adhi Karya Tbk shares.